Implementation of Problem Based Learning in Writing Persuasive Texts in Indonesian Language Course - Lazfihma Lazfihma; Padi Utomo; Rio Kurniawan; Dwi Ismawati; Dwi Lyna Sari; Meli Afrodita (EDUJAVARE: International Journal of Educational Research, 2026)
Writing skills are one of the most important language skills in the academic world. This study aims to (1) examine the stages of implementation of the Problem Based Learning (PBL) learning model (2) describe the implementation of the Problem Based Learning (PBL) learning model in learning to write persuasive texts in the General Indonesian language course. The method used is descriptive qualitative research with a case study design. The research subject is a first-semester student of the University of Bengkulu. Data collection techniques include observation, interviews, documentation, and writing tests (pretest and posttest). Data analysis is carried out using an interactive analysis model that includes three stages: data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of PBL runs through five main stages, namely: problem identification, task organization, independent investigation, preparation of solutions in the form of persuasive texts, and evaluation/reflection. Problem Based Learning is effectively applied in learning to write persuasive texts and can be used as an alternative approach to learning Indonesian in higher education.